PENINGKATAN PERILAKU PENCEGAHAN LUKA DIABETIK DENGANEDUKASI PERAWATAN KAKI BERBASIS FAMILY SUPPORT: ENHANCEMENT OF DIABETIC WOUND PREVENTION BEHAVIOR WITHFAMILY SUPPORT-BASED FOOT CARE EDUCATION - Dyah Restuning Prihati; Heny Prasetyorini (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Background: Management of diabetes mellitus is not only from pharmacology but requires family support. The role of the family in diabetic foot care is needed to improve the quality of life of patients with diabetes mellitus. The purpose of this study was to analyze the behavior of diabetic wound prevention after being given Family Support-Based Foot Care Education. Method, this type of research is a quasi-experimental one-group pre-post test with the intervention of Family Support-Based Foot Care Education. The instrument for measuring foot care behavior uses the NAFF (Nottingham Assessment of Functional Footcare) questionnaire. The results showed that before being given family support-based foot care education, there were 20 respondents with negative behavior and 30 respondents with positive behavior. Data analysis using the Wilcoxon Signed Rank Test obtained a p-value of 0.000 so that a p-value <0.05 there were differences in foot care behavior before and after being given family support-based foot care education to the respondents. Conclusion: The results showed that there was an increase in diabetic wound prevention behavior with an average increase of 10.5.